2021
DOI: 10.24349/o7z8-gxu4
|View full text |Cite
|
Sign up to set email alerts
|

Predation capacity of soil-dwelling predatory mites on two major maize pests

Abstract: The western corn rootworm Diabrotica virgifera virgifera (WCR), and the wireworm Agriotes sordidus (WW), whose eggs and first instar larvae develop in the first few centimeters of soil, are major crop pests. As soil-dwelling predatory mites are known as potential biocontrol agents against many pests, we investigated the predation capacity of Stratiolaelaps scimitus, Gaeolaelaps aculeifer and Macrocheles robustulus on immature stages of WCR and WW in a laboratory setting. While eggs of WCR and WW were never con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 10 publications
0
4
0
Order By: Relevance
“…The studies revealed predatory potential of S. scimitus against a harmful phytophage -western corn rootworm Diabrotica virgifera LeConte, 1868 (Coleoptera, Chrysomelidae). This mite prefers first-age larvae of D. virgifera rather than eggs (Pasquier et al, 2021). Diet of female D. virgifera does not affect the further dietary preferences of S. scimitus.…”
Section: Introductionmentioning
confidence: 78%
“…The studies revealed predatory potential of S. scimitus against a harmful phytophage -western corn rootworm Diabrotica virgifera LeConte, 1868 (Coleoptera, Chrysomelidae). This mite prefers first-age larvae of D. virgifera rather than eggs (Pasquier et al, 2021). Diet of female D. virgifera does not affect the further dietary preferences of S. scimitus.…”
Section: Introductionmentioning
confidence: 78%
“…The latter is known to feed on SCR eggs [60] and laelapid mites, including in the genus Stratiolaelaps, attack NCR and WCR eggs [63,64], with S. scimitus consuming WCR eggs under lab conditions [64]. However, Pasquier et al [110] did not find that S. scimitus attacked WCR eggs in lab experiments. Tyrophagus putrescentiae feeds on a wide variety of food, e.g., plants, stored products, fungi, and nematodes [80,81], and is able to adapt and persist on nutritionally-different diets [111] and tolerate some mycotoxins and plant-based spices [112], which could be why NCR egg consumption was similar among treatments for this mite species.…”
Section: Discussionmentioning
confidence: 99%
“…This creates direct damage leading to yield loss (Riedell 1990 ; Sutter et al 1990 ; Spike and Tollefson 1991 ; Godfrey et al 1993 ; Gray et al 2009 ). Laboratory studies showed promising results when testing predatory soil mites against this pest; field experiments, however, gave mixed results (Prischmann-Voldseth et al 2011 ; Prischmann-Voldseth and Dashiell 2013 ; Pasquier et al 2021a , b ).…”
Section: Predator-prey Systemsmentioning
confidence: 99%